KAPASITAS VITAL PARU BERKORELASI POSITIF DENGAN KEMAMPUAN TAHAN NAFAS PADA LAKI-LAKI USIA 19-25 TAHUN - Putra, Kukuh Pambuka; Pratama, Rizal Putra; Nugroho, Kristiawan Prasetyo Agung (Journal of Sport Science and Education, 2020)
Freediving is a diving activity without any breathing equipments. The durations of the dive activity depend on ability to hold breath (apnea). The ability of apnea may be affected by lung vital capacity. The purpose of this study is to find out the relationship between vital lung capacity and apnea duration in 30 males 19-25 years old. Vital lung capacity measured using spirometer and the duration of apnea measured using stopwatch in swimming pool. Data analyzed using 1-tailed pearson correlation test. The result shows that there is a correlation (p<0,05) between vital lung capacity and the duration of apnea. The correlation coeficient is 0,743 that means this is a strong positive correlation between the two variables.Keywords: Apnea; Diving; Freedive; Lung; Vital Capacity.